The Influence of Learning Outcomes on Students’ Career Choices at Shailendra High School Palembang - Maharani Widya Puspa; Edi Harapan; Nurlela Nurlela (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to determine the relationship or influence of learning outcomes on career choices for students at Shailendra High School Palembang. Bearing in mind that during the initial visit the researcher primarily consulted regarding students' career choices, for this reason there is something that this research wants to achieve, namely to find out the influence or relationship between learning outcomes and students' career choices at Shailendra High School Palembang. The method used in this research is a quantitative correlation type method which seeks to determine the relationship or influence or connection between the two variables in this research X and Y. In taking samples in this research using a purposive sampling technique with a total of 75 students from part of the population. The results of research and data analysis show that there is an influence or relationship and a small relationship on the intensity of learning outcomes (X) on career choice (y). Obtaining R Square data of 0.06, this value is converted into a percentage of the results obtained, 0.06 x 100% = 0.6, so it can be said that the influence or relationship between variable X and variable Y is only 0.6. This means that there is a relationship or influence or relationship between the intensity of learning outcomes and career choices, but at a small or low level. So it can be concluded that there is a small influence or relationship between learning outcomes on students' career choices at Shailendra High School Palembang.